Anaerobic digestion of domestic wastewater in different salinity levels: the adaptation process - Idrus, Syazwani; Nik Daud, Nik Norsyahariati; Ahsan, Amimul (Universiti Putra Malaysia Press, 2017)
The effect of osmotic stress was carried out to determine the resistance to salt toxicity using 4 Continuous Stirred Tank Reactor (CSTR). A CSTR digestion study revealed that digesters seeded with an inoculum from a conventional mesophilic digester treating municipal wastewater and fed on domestic wastewater (DW) plus salts were able to acclimate successfully to a final salt concentration of 10 g l-1. The digesters showed some disturbances during the acclimatisation period as indicated by reductions in specific methane production (SMP), specific biogas production (SBP), pH and increases in Intermediate Alkalinity /Partial Alkalinity (1A/PA) ratio and Volatile Fatty Acid (VFA) concentration. This study revealed the order of disturbance was Sodium Chloride (NaCl) > Potassium Chloride (KCl) > KCl + NaCl. The average values for SMP after stabilisation were below those in the controlled digester, at 0.335 (controlled), 0.323 (NaCl), 0.316 (KCl + NaCl) and 0.308 l CH4 g-1 COD added (KCl).